Community participation for sustainability of rural water schemes: a case of CHAMAVITA water schemes in Lushoto District - Mdendemi, Patience Placid (Mzumbe University, 2024)
A dissertation submitted in partial fulfillment of the requirements for the degree of Master of Science in Environmental Management (MSc. EM) of Mzumbe University